Dampak Inflasi Terhadap Pertumbuhan Ekonomi Indonesia (PDB) Periode 2019-2023 - Ayudana Kezia Pasaribu; Muhammad Aryo Fachrezi; Ranjani Nuralifah; Reyhani Intan Sabrina; Irena Breta BR Surbakti; Nurlela Nurlela; Disya Ayu (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This study is intended to understand the impact of inflation on economic growth in the last five years using a simple linear regression method processed using a statistical package for the social sciences (SPSS) program. The results of the analysis that have been investigated revealed that, obtained a significance value of 0.338 which is greater than 0.05, this shows that inflation does not have a major impact on economic development. Based on the coefficient of determination test, the R² is 30% < 55%, which means that inflation can only explain or affect economic growth (GDP) by 30%, while the other 70% is influenced by other variables. The final conclusion obtained is that in the last five years (2019-2023), inflation does not affect economic growth (GDP), this may be because the value of inflation and GDP in the last five years (2019-2023) is stable, so it does not show a significant influence.